2019
DOI: 10.3390/w11112418
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of Water Isotopes and Water Source Identification During the Wet Season in Naqu River Basin, Qinghai–Tibet Plateau

Abstract: Climate change is affecting the discharge of headstreams from mountainous areas on the Qinghai–Tibet Plateau. To constrain future changes in discharge, it is important to understand the present-day formation mechanism and components of runoff in the basin. Here we explore the sources of runoff and spatial variations in discharge through measurements of δ2H and δ18O in the Naqu River, at the source of the Nu River, on the Qinghai–Tibet plateau, during the month of August from 2016 to 2018. We established thirte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 41 publications
0
4
0
Order By: Relevance
“…In general, mainstream and tributary river water have similar seasonal differences (Li et al 2016b). However, the isotopic values of the mainstream and tributary river water were different in study area, which may be related to the evaporative fractionation and the recharge source of river water (Chen et al 2019). In spring, the main recharged sources of tributary river water were snow and permafrost meltwater, resulting in isotope values of river water lower.…”
Section: Differences In Stable Isotopes Of Plants Watermentioning
confidence: 81%
“…In general, mainstream and tributary river water have similar seasonal differences (Li et al 2016b). However, the isotopic values of the mainstream and tributary river water were different in study area, which may be related to the evaporative fractionation and the recharge source of river water (Chen et al 2019). In spring, the main recharged sources of tributary river water were snow and permafrost meltwater, resulting in isotope values of river water lower.…”
Section: Differences In Stable Isotopes Of Plants Watermentioning
confidence: 81%
“…As scarce local rainfall inputs cannot offset for the water loss ( Ma et al., 2014 ; Dong et al., 2016 ), another recharge source is essential. There are conflicting opinions regarding the regional water cycle ( Chen et al., 2014 ; Zhan et al., 2018 ; Wang et al., 2021 ). Some researchers have concluded that local rainfall does not contribute substantially to the regional water systems ( Chen et al., 2005 ; Dong et al., 2016 ; Jin et al., 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…The vertical profile of the soil water isotope composition integrates the processes involved in rainfall replenishment, groundwater recharge, blending with pre-existing water, and evaporation ( Tang and Feng, 2001 ; Brooks et al., 2015 ; Wang J. et al., 2019 ). Isotopic enrichment of the surface soil ( Figures 4 , 5 ) was influenced by evaporation ( Zhou et al., 2019 ), as well as evaporative water vapor condensation ( Chen et al., 2014 ), of which strong evaporation resulted in a lower SWC in this layer ( Figure 2 ). In comparison, the deeper soil water contains less heavy isotopes than the shallower layers, primarily attributable to the fact that deep soil layers were less influenced by evaporation and more affected by capillary upward recharge of groundwater containing light isotopes ( Wu et al., 2018 ; Zhou et al., 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…The Naqu River, which is 460 km long, covers 16,350 km 2 of total drainage area [20]. The Naqu River is composed of four main tributaries, which are, Chengqu, Mugequ, Gongqu, and Luoqu from north to south [21]. Most of the Naqu River basin is located in a plateau subfrigid monsoon semi-humid climate zone, with intensive solar radiation and thin air.…”
Section: Study Areamentioning
confidence: 99%